2020
DOI: 10.1055/s-0040-1716343
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorder and Hepatitis C Prevention and Care in People Who Inject Drugs: The State of Play

Abstract: Safe and effective treatment with direct-acting antivirals (DAAs) has ushered in an era in which hepatitis C virus (HCV) elimination, as set out by the World Health Organization, is possible. However, alcohol use disorder (AUD) has the potential to reduce the benefits of prevention interventions and reduce access to and continuity of HCV care in at-risk populations, such as people who inject drugs (PWID). We review the literature on the consequences of AUD on the effectiveness of HCV prevention and the cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In the DAA era, AUD is common in patients diagnosed with decompensated cirrhosis 40 and hepatocellular carcinoma and remain as a major contributor to the HCV-related liver disease burden. In our study, we confirmed that cirrhosis occurred more frequently in people with AUD in comparison with people without AUD.…”
Section: Discussionmentioning
confidence: 99%
“…In the DAA era, AUD is common in patients diagnosed with decompensated cirrhosis 40 and hepatocellular carcinoma and remain as a major contributor to the HCV-related liver disease burden. In our study, we confirmed that cirrhosis occurred more frequently in people with AUD in comparison with people without AUD.…”
Section: Discussionmentioning
confidence: 99%